Inisiasi Tunas Kokoleceran (Vatica bantamensis) pada Berbagai Jenis Media Tanam dan Konsentrasi BAP (Benzyl Amino Purine) Secara In Vitro - Sri Sudiyanti; Tubagus Bahtiar Rusbana; Susiyanti Susiyanti (Jurnal Agro, 2017)
Kokoleceran (Vatica bantamensis) is an endemic plant of Banten which is only in Ujung Kulon, and has been designated as identity of Banten province. Now the existence of Kokoleceran has been endangered. Based on data from the IUCN, since 1998 there has been no research. Kokoleceran initiation needs technology for preventing from the extinction. One of the mass propagation is through the technique culture in vitro. This research aimed to get the precise medium and BAP concentration for Kokoleceran, and knowing the response of Kokoleceran growth in in vitro. This research was done in November 2015 until March 2016 at the Laboratory of Biotechnology, Department of Agroecotechnology, Faculty of Agriculture, University of Sultan Ageng Tirtayasa, Serang, Banten. This research used Completely Randomized Design (CRD) two factors. The first factor was medium that were MS and WPM media. The second factor was BAP concentration which consisted of four levels namely 0 mg L-1, 1 mg L-1, 2 mg L-1, and 3 mg L-1. The results showed that the use of different media and BAP concentrations had no impact on the time appear of shoot, shoot number, and root number. There was effect from both treatments on medium color, and growing of callus on the explants.